Direct role for proliferating cell nuclear antigen in substrate recognition by the E3 ubiquitin ligase CRL4Cdt2. - Havens, C; Shobnam, N; Guarino, E; Centore, R; Zou, L; Kearsey, S; Walter, J (2012)
The E3 ubiquitin ligase Cullin-ring ligase 4-Cdt2 (CRL4(Cdt2)) is emerging as an important cell cycle regulator that targets numerous proteins for destruction in S phase and after DNA damage, including Cdt1, p21, and Set8. CRL4(Cdt2) substrates contain a "PIP degron," which consists of a canonical proliferating cell nuclear antigen (PCNA) interaction motif (PIP box) and an adjacent basic amino acid. Substrates use their PIP box to form a binary complex with PCNA on chromatin and the basic residue to recruit CRL4(Cdt2) for substrate ubiquitylation. Using Xenopus egg extracts, we identify an acidic residue in PCNA that is essential to support destruction of all CRL4(Cdt2) substrates. This PCNA residue, which adjoins the basic amino acid of the bound PIP degron, is dispensable for substrate binding to PCNA but essential for CRL4(Cdt2) recruitment to chromatin. Our data show that the interaction of CRL4(Cdt2) with substrates requires molecular determinants not only in the substrate degron but also on PCNA. The results illustrate a potentially general mechanism by which E3 ligases can couple ubiquitylation to the formation of protein-protein interactions.